Analogi dalam tafsiran ungkapan bahasa Melayu: ''matahari sepenggalah tingginya'' (Jurnal Bahasa, 2007)
Malay uses a certain group of derivative nouns to express measurements of 'time ' and 'space '. These words are derived by the addition of an affix pe(N)-, preceded by numerals. The characteristics of the grammatical structure of such derivatives can be examined analogically in relation to me(N)- verbs derived from the same root words. This means that the pe(N)- derivatives are to be explained as action nouns (nomina actionis). However, it seems difficult to explain the derivative (se-)penggalah ( < galah) used in such expressions as "matahari sepenggalah tingginya" in the same way by assuming an action verb menggalah as its base. This article aims at firstly explaining the meaning oft he affix pe(N)contained in the derivative (se-) penggalah from the grammatical point of view, and secondly interpreting more or less scientifically the expression "matahari sepenggalah tingginya" as it portrays a natural phenomenon. In explicating the second case, a link will be made to its basis, Islamic astronomy (ilmu falak). This kind of heritage of Malay science is still manifested in the structure of the Malay language.